Техническое перевооружение ТЭЦ-2 «Эсхар» - Левин, М. М.; Руденко, С. Н.; Мамонтов, Н. И.; Бабичев, Л. А. (НТУ "ХПИ", 2006)
Розглянуто варіанти технічного переозброєння ДП ТЕЦ-2 «Есхар» з урахуванням наявної інфраструктури електростанції. Показано переваги будівництва вугільних дубль-блоків 125 МВт з котлами ЦКШ порівняно із зведенням парогазових блоків 135 МВт враховуючи можливість значного відпуску тепла.

The variants of modernisation SM TPP-2 "Eshar" was considered in view of anavailable infrastructure of power station. The advantage of construction of coal doubles–blocks 125 megawatt with boiler CBL is shown in comparison with construction "steamand gas blocks" 135 megawatt in view of an opportunity of significant tempering of heat.
Modernisation of the TPP-2 "Eshar"
Keywords: котлотурбинное оборудование; котлы-утилизаторы; паровые турбины; природный газ; пылеугольные блоки; теплоснабжение